COMPARISON OF PEAK EXPIRATORY FLOW RATE AND LIPID PROFILE IN ASYMPTOMATIC SMOKERS AND NON-SMOKERS - Fatima, Fozia; Fatima, Sadia; Noor, Muhammad Munir; Abbasi, Munir Ahmad; Jadoon, Raheel Jahangir; Sohail, Muhammad; Shah, Muhammad Junaid; Ullah, Sana (Journal of Ayub Medical College Abbottabad, 2015)
Background: Tobacco is the major risk factor for chronic obstructive airway disease (COAD), other pulmonary diseases, cancer, cardiovascular and cerebrovascular diseases. The objective of study was to determine the mean Peak Expiratory Flow Rate (PEFR) and serum lipid profile in apparently healthy male smokers and non-smokers. Methods: This cross-sectional study was conducted in Ayub Teaching Hospital, Abbottabad from 15th December, 2009 to 15th June, 2010. Apparently healthy smokers and non-smokers from population coming to Hospital as attendants of the patients or as employees of the hospital were inducted in the study. PEFR and lipid profile of all the subjects was accessed. Results: There were total of 300 male subjects, 150 smokers and 150 non-smokers. The mean age of study subjects was 26.60±5.5 years. The mean PEFR of smokers was 450.62l/min and that of non-smokers was 494.81 L/min, the difference being statistically significant (p-value <0.05).The mean total cholesterol of smokers is 5.30±0.86 mmol/l and it was 3.84±0.54 mmol/l in non-smokers. Mean serum Triacyl Glycerols (TAGs) and Low Density Lipoproteins (LDL) cholesterol of smokers was 2.04±0.38 and 3.5±0.83 mmol/l whereas it was 1.44±0.52 and 2.02±0.66mmol/l in non-smokers. Mean High Density Lipo-protein (HDL) of smokers was 0.86±0.30mmol/l and of non-smokers is 1.20±0.41mmo/l. There was statistically significant difference between serum lipid profile of smokers and non-smokers (p<0.05). the mean serum Total Cholesterol (TC), TAGs and LDL were significantly higher in smokers as compared to non-smokers. However HDL was significantly lower in smokers in comparison to non-smokers. Conclusion: There was statistically significant difference between PEFR of smokers and non-smokers. Higher and significant mean values of TC, TAG and LDL-C was observed in smokers as compared to non-smokers. Keywords: Peak Expiratory Flow Rate, smoker, lipid profile, Triacyl Glycerol, Low Density Lipoproteins